Giant unicystic ameloblastoma of maxilla-successful endoscopic management - Mohanty, Sanjeev; Vergis, Manu; V., Devipriya; G., Haripriya; Nallapaneni, Lakshmi Shree; Nallapaneni, Pravilika Parachur (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
This 32-year-old male patient presented with complaints of restricted mouth opening and gross facial asymmetry owing to the massive jaw swelling on the right side. After a thorough examination, a diagnosis of unicystic ameloblastoma of maxilla. Although, the standard of care surgical approach was through Weber-Fergusson incision, a concerted attempt to excise the tumour with the minimally invasive endoscopic route was made successfully. The patient was symptom free now with complete resolution of swelling on a regular follow up post operatively. This case report highlighted the modern day protocol of organ preservation concepts in surgical management of a rare tumour in otolaryngology practice